The Effectiveness of Problem-Based Learning Models on Critical Thinking Ability and Social Sensitivity in Social Studies Subjects at SDN 105 Baraka Enrekang Regency - Rasdianah Muri; Nursalam Nursalam; Muhammad Nawir (Universitas Muhammadiyah Enrekang, 2022)
This study aimed at determining the effectiveness of the problem-based learning model on critical thingking skills and social sensitivity in social studies subjects at SDN 105 Baraka Kab. Enrekang. This research was a quantitative research using quasi experimental methods. The desigh used in this study was a nonequivalent group pretest-posttest design. The population in this study were all students of SDN 105 Baraka,Enrekang Regency while the samples were students of class VA and VB at SDN 105 Baraka,Enrekang Regency . The research instrumens used were question sheets, questionnaires and observation sheets. The date analysis technique used was an analytical test which consisted of a normality and homogeneity test followed by hypothesis test. The results of this study indicate the effectiveness of the problem-based learning model on thinking skills and social sensitivity in social studies subjects was effectively used, judging by the results of the hypothesis testing using the independent sample t-test using SPSS version 21 seen in the sig column. (2-tailed) was the value of 0.007 < 0.05. In this study, a sample of 36 students was taken, so the value of degrees of freedom (dk) was = n-2 = 36-2 = 34 and the error rate was 5%. Because for the 2-sided test (0.05: 2 = 2.5%) it can be seen that the value of T-table = 2.032. T-count = 2.875 can be seen from the column Equal variances assusmed (homogeneous), it can be seen that the value of Tcount = 2.875. So it can be seen that Tcount > Ttable was 2.875 > 2.032 with a significance was 0.007 < 0.05. So it can be concluded that Ho is rejected and Ha is accepted (the use of problem-based learning models is effectively used for social studies learning in fifth grade students of SDN 105 Baraka.